Analysis of Brondolan Fruit Loss in Palm Oil Harvesting Activities in the Case Study of Sentekan Estate PT Rea Kaltim Plantations - Sukariyan; Arief Rahman; Rossy Mirasari; Pandu Rochman Suosa Putra; Dea Ayu Rahmadini (Jurnal Loupe, 2024)
Brondolan is an oil palm fruit that is separated from spikelets because it is too ripe during harvesting activities. Apart from that, brondolan is part of the fresh fruit bunch which produces maximum quality Crude Palm Oil (CPO). The aim of this research is to analyze losses from harvesting activities in the form of oil palm fruit stalks. The research method is to carry out quantitative and descriptive analysis. Loss of brondolan fruit during palm oil harvesting activities from the research sample was 10% of the sample block area in the disk area, pickle market area and yield collection area (TPH), amounting to 16,946 Kg/month of the total Kg/division oil palm fruit production. This occurs because the fruit is abandoned or left behind as a result of weak supervision and poor maintenance or maintenance activities in the plate area, pickle market area and TPH area which are not controlled by the growth of weeds, kentosan, this has an impact on the potential loss of 3,2% of total TBS production in the division.